(untitled) (Global Journal of Science Frontier Research, 2012)
Neck muscles of the rolling pigeons are excited through shaking or auto or continuous excitation. Though the tumbling is backward; the neck muscle is a great factor for this. Flying tumbler pigeon rolls during flying; here flying velocity and height is a fator but parlor tumbler when fly its neck muscles not excited. Lateral shaking is responsible for tumbling not shakes of dorso-ventrally. Normally tumblers are two types that are tumbler and roller. Then tumbler divides house or parlor tumbler and flying tumbler. On the other hand roller or parlor rollers are two types which are autoroller and shaking/non shaking roller. In the tumbler pigeon family there are a lot of flying tumblers (fly at night, great height), tippler (fly 22 hours, first in UK in 1971) by the cross between tumbler and Cumulet (fly 10 hours) from France (sustained flight, rapid tumble, short flying tumbling, auto tumbler), highflier (fly 15 hours, elongated body) but only dasti (common) tumbles till tired, kalami (strike on the beak), havai (short tumble then fly), auto parlor tumblers (like epilepsy disease) excited any internal and external factors which induces chemical reaction for tumbling. Anticonvulsant drugs are effective on pigeons tumbling.